Peer Feedback in Reviewing Essay - Dewi, Utami (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
Peer feedback is the comment or advice from equal partner, which can help the writer to improve their product of the writing. The aim of this study was to find out the types of peer feedback most frequently given by students in reviewing their classmatesÃ¢â‚¬â„¢ essay. The total participants of this study were 178 students of English education department. The data of this study was taken from peer feedback given by students in reviewing essay, which applied in the class of writing. The design of this study was descriptive quantitative. The peer feedback given by students in reviewing their classmatesÃ¢â‚¬â„¢ essay was analyzed and categorized based on Hyland and HylandÃ¢â‚¬â„¢s classification: praise, criticism, and suggestion. As the result, suggestion was most frequently given by students in reviewing essay because most of the students gave constructive comment or asking the improvement as their feedback rather than gave praise and criticism. It was seen that the total suggestion which given by students to the classmates was 208 feedback. Then, 108 praise was given which expressed the positive comments or positive impression, though there is some empty praise without constructive comments. 107 criticisms were also given by students in expressing their negative comment or dissatisfaction with the essay written by their classmates. In addition, some combinations of the feedback were also given in reviewing essay.Ã‚Â There are 30 combinations of praise and criticism, 51 combinations of praise and suggestion, and 25 combinations of criticism and suggestion. In conclusion, the reviewers expressed positive and negative comments, positive and constructive comments, the negative and constructive comments in same time.